Persistent alterations in gray matter in COVID-19 patients experiencing sleep disturbances: a 3-month longitudinal study - Kaixuan Zhou; Gaoxiong Duan; Ying Liu; Bei Peng; Xiaoyan Zhou; Lixia Qin; Lingyan Liang; Yichen Wei; Qingping Zhang; Xiaocheng Li; Haixia Qin; Yinqi Lai; et al. (Neural Regeneration Research)
Sleep disturbances are among the most prevalent neuropsychiatric symptoms in individuals who have recovered from severe acute respiratory syndrome coronavirus 2 infections. Previous studies have demonstrated abnormal brain structures in patients with sleep disturbances who have recovered from coronavirus disease 2019 (COVID-19). However, neuroimaging studies on sleep disturbances caused by COVID-19 are scarce, and existing studies have primarily focused on the long-term effects of the virus, with minimal acute phase data. As a result, little is known about the pathophysiology of sleep disturbances in the acute phase of COVID-19. To address this issue, we designed a longitudinal study to investigate whether alterations in brain structure occur during the acute phase of infection, and verified the results using 3-month follow-up data. A total of 26 COVID-19 patients with sleep disturbances (aged 51.5 ± 13.57 years, 8 women and 18 men), 27 COVID-19 patients without sleep disturbances (aged 47.33 ± 15.98 years, 9 women and 18 men), and 31 age- and gender-matched healthy controls (aged 49.19 ± 17.51 years, 9 women and 22 men) were included in this study. Eleven COVID-19 patients with sleep disturbances were included in a longitudinal analysis. We found that COVID-19 patients with sleep disturbances exhibited brain structural changes in almost all brain lobes. The cortical thicknesses of the left pars opercularis and left precuneus were significantly negatively correlated with Pittsburgh Sleep Quality Index scores. Additionally, we observed changes in the volume of the hippocampus and its subfield regions in COVID-19 patients compared with the healthy controls. The 3-month follow-up data revealed indices of altered cerebral structure (cortical thickness, cortical grey matter volume, and cortical surface area) in the frontal-parietal cortex compared with the baseline in COVID-19 patients with sleep disturbances. Our findings indicate that the sleep disturbances patients had altered morphology in the cortical and hippocampal structures during the acute phase of infection and persistent changes in cortical regions at 3 months post-infection. These data improve our understanding of the pathophysiology of sleep disturbances caused by COVID-19.